2012
DOI: 10.1007/s00401-012-0997-1
|View full text |Cite
|
Sign up to set email alerts
|

Heparanase overexpression impairs inflammatory response and macrophage-mediated clearance of amyloid-β in murine brain

Abstract: Neuroinflammation is typically observed in neurodegenerative diseases such as Alzheimer’s disease, as well as after traumatic injury and pathogen infection. Resident immune cells, microglia and astrocytes, are activated and joined by blood-borne monocytes that traverse the blood–brain barrier and convert into activated macrophages. The activated cells express various cytokines, chemokines and proteolytic enzymes. To study the role of heparan sulfate proteoglycans in neuroinflammation, we employed a transgenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
69
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 62 publications
2
69
1
1
Order By: Relevance
“…We regard such experiments to be the subject for separate studies. We do not rule out that additional factors, like differential immune response and HS fragment-mediated A␤ clearance along the perivascular lymphatic drainage pathway (15,34,35), also influence parenchymal and cerebrovascular A␤ deposition in double-transgenic mice.…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…We regard such experiments to be the subject for separate studies. We do not rule out that additional factors, like differential immune response and HS fragment-mediated A␤ clearance along the perivascular lymphatic drainage pathway (15,34,35), also influence parenchymal and cerebrovascular A␤ deposition in double-transgenic mice.…”
Section: Discussionmentioning
confidence: 87%
“…However, the cause and effect of this codeposition remains unclear. To understand whether HS and HSPGs are active participators of A␤ pathogenesis or simply adhere to and colocalize with A␤ in amyloid plaques, we generated a double-transgenic mouse model overexpressing both human heparanase and human A␤PP harboring the Swedish mutation (tgHpa*Swe) by crossing the tgHpa (15) and tgSwe (25,26) mice. We found that the double-transgenic mice showed overexpression of heparanase in the brain and produced shorter HS fragments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations